2020
DOI: 10.1016/j.devcel.2019.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Control over mTOR-Dependent Diapause-like State

Abstract: Regulation of embryonic diapause, dormancy that interrupts the tight connection between developmental stage and time, is still poorly understood. Here, we characterize the transcriptional and metabolite profiles of mouse diapause embryos and identify unique gene expression and metabolic signatures with activated lipolysis, glycolysis, and metabolic pathways regulated by AMPK. Lipolysis is increased due to mTORC2 repression, increasing fatty acids to support cell survival. We further show that starvation in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
118
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(123 citation statements)
references
References 96 publications
(103 reference statements)
5
118
0
Order By: Relevance
“…Importantly, we propose that the dynamics of the paused stage, embryonic diapause are affected by microRNA regulated stress and inflammation response genes. This is interesting in the light of recent publications that have revealed importance of stress response and inflammation in regulation of embryonic diapause and stem cell quiescence [35,88,89], and calls for further analysis on microRNA contribution in stress induced regulation of pause in development.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Importantly, we propose that the dynamics of the paused stage, embryonic diapause are affected by microRNA regulated stress and inflammation response genes. This is interesting in the light of recent publications that have revealed importance of stress response and inflammation in regulation of embryonic diapause and stem cell quiescence [35,88,89], and calls for further analysis on microRNA contribution in stress induced regulation of pause in development.…”
Section: Resultsmentioning
confidence: 98%
“…The transition from pre-to-post-implantation can be suspended in an intermediate state called diapause. To obtain a more complete picture of microRNAs potentially involved in regulating the diapause state, we combined a publicly available microarray-based profiling of diapause and re-activated embryos [37] with our RNA-seq of diapause and post-implantation embryos [35], using the strategy outlined in Figure 1A. We identified 379 consistent connections between 38 microRNA and 274 target genes, where a microRNA is up (down)-regulated, and its target gene is down (up)-regulated (Table S7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mTOR signalling pathway (integrated by two mTOR containing complexes, mTORC1 and mTORC2) is a global regulator of translation, and maintains cellular energy homeostasis in response to extra-cellular stimuli such as growth factors and nutrient availability 47 . As part of mTORC1, mTOR specifically controls transcription and translation of ribosomal proteins, synthesis and processing of rRNAs and ribosome biogenesis, assembly and availability, that ultimately dictates general translation of all mRNA transcripts (mTORC2 is associated with co-translational protein degradation and lipolysis) 47,[63][64][65][66] . It was recently demonstrated that a prolonged state of in vitro developmental diapause (lasting 9-12 days) can be chemically induced in early stage (E3.5) mouse blastocysts upon dual inhibition of the mTORC1 and mTORC2, mimicking naturally occurring in vivo diapause 41 .…”
Section: Discussionmentioning
confidence: 99%